(untitled) (Education in the 21st Century, 2021)
The values of the 21st century lead perceptions to globalization, today the media has invaded all spheres of our lives. The media play an integral role in the lives of young people from an early age. The informational, educational, educational role of the media in the development of the child’s worldview and moral values cannot be denied. It is indisputable that in the current information age one of the most powerful means of educating a primary school student, developing his thinking, and shaping his worldview is the media. In this sense, the media can even become a reliable ally of education, acting as a source of openness to the outside world. The modern school must now teach children how to control the language of the media, how to become active, informed users of education. The media has started to have a great influence on the formation of children’s views. From this point of view, it is necessary to start preserving appropriate pedagogical conditions for the use of media education from primary school, aimed at developing children’s health and safety behavior, their socialization, making the establishment and maintenance of teacher-parent cooperation in this process. Many teachers use the media to increase the effectiveness of their lessons. Therefore, the opportunities provided by the media can be used to train citizens with high personal qualities and full members of society.